Analiza i praktyczne uwagi w zakresie konstrukcji i stosowania prawa do bycia zapomnianym w UE - Rojszczak, Marcin (Wydawnictwo C.H. Beck, 2017)
Legal regulations connected with the protection of personal data are evolving in the direction of granting the individuals an effective control of information concerning them, published on the Internet. In the world of forefront of developments in this field for many years is the European Union, in which individual rights and freedoms are permanently enshrined in the Charter of Fundamental Rights. Uncompromising protection of individual rights is encouraged by both the EU legislature, as well as the judgments of the constitutional courts of the Member States and the European Court of Justice. The purpose of this article is to present the most important principles of the right to be forgotten and to analyze whether the current form of this law, which is a consequence of the ECJ rulings, does not contribute to the weakening of other fundamental rights such as the right to information and freedom of expression.
Keywords: the right to be forgotten; privacy; the right to erasure; censorship; GDPR